Tratamiento contable tributario de la devolución del IVA y su impacto en la liquidez del sector florícola de la provincia de Cotopaxi - Pérez Cedeño, Linda Nicols (2022)
This research analyzes the process of refunding the Value Added Tax VAT to exporters of goods and services in the Latacunga canton, Cotopaxi’s province, Ecuador, diagnoses the financial liquidity situation of companies in reference to this process and presents a technical report that gives response to the shortcomings found with the aim of optimizing this process in terms of time and resources. The content of this thesis work is developed in four chapters as follows................